Work-related mental health problems increase with rising aggregate unemployment - Anna Katharina Pikos (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2018)
This paper analyzes the relationship between work-related mental health of the German working population and unemployment on the occupation-region level measured one year before the outcome. Rising unemployment is significantly associated with a higher risk for emotional strain, emotional exhaustion, absenteeism, and presenteeism among employed individuals. Occupation specific unemployment drives this relationship, while the regional dimension is less important. The relationship is driven by individuals with own past unemployment experience.
Keywords: I10; J64; 330; work-related mental health; unemployment; emotional exhaustion; emotional strain